2014
DOI: 10.3233/xst-140457
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and post-treatment CT appearance of biopsy proven mixed cryptococcus and candida cholangitis

Abstract: Cryptococcus neoformans and Candida are common opportunistic pathogens of human. There is very limited literature on Cryptococcus neoformans cholangitis or Candida cholangitis in immunocompetent patient while mixed Cryptococcus neoformans and Candida cholangitis has not been reported in the literature ever before. We hereby report the imaging findings of a case of mixed Cryptococcus neoformans and Candida cholangitis in an immunocompetent boy. The CT features included nodules in the cystic duct and common bile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Bacteria that are often co-isolated with Candida spp. from infection sites are staphylococci [10,316], but also less frequent bacteria such as S. marcescens , Tropheryma whipplei or other fungi, for example, C. neoformans [317,318,319].…”
Section: Fungal-bacterial Interactions—niche By Nichementioning
confidence: 99%
“…Bacteria that are often co-isolated with Candida spp. from infection sites are staphylococci [10,316], but also less frequent bacteria such as S. marcescens , Tropheryma whipplei or other fungi, for example, C. neoformans [317,318,319].…”
Section: Fungal-bacterial Interactions—niche By Nichementioning
confidence: 99%
“…Fluconazole for 8weeks. / (Luo et al, 2014) 4 5 M Upper abdominal pain, jaundice, mild hepatosplenomegaly CT showed CBD with incomplete bile duct obstruction. Ultrasound demonstrated irregular mural thickening of the CBD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[404][405][406] In contrast, immunocompetent patients tend to present with an isolated biliary infection that clinically and radiologically mimics sclerosing cholangitis or cholangiocarcinoma. [407][408][409][410][411][412] These patients exhibit obstructive jaundice, and radiologic studies may show dilatation of intrahepatic bile duct dilatation, stricturing and wall thickening of extrahepatic bile ducts, and masslike lesions in the hilum. Most reported immunocompetent patients with biliary cryptococcosis are children or young adults.…”
Section: Cryptococcosismentioning
confidence: 99%
“…Most reported immunocompetent patients with biliary cryptococcosis are children or young adults. [407][408][409]412 Histopathologically, immunocompetent cases are characterized by granulomas, whereas in AIDS patients, an inflammatory reaction is poorly developed or absent. Autopsies in cases of disseminated infection have shown areas of necrosis with innumerable yeast cells, yeast cells diffusely within tissue admixed with cellular debris and inflammation, or yeast cells within Kupffer cells ( Fig.…”
Section: Cryptococcosismentioning
confidence: 99%